Corporate governance mechanisms and unmanaged earnings: evidence from Government Linked Companies (GLCs) - Mohammed Shawtari, Fekri Ali; Mohamad, Muslim Har Sani; Ab. Rashid, Hafiz Majdi; Salem, Milad Abdelnabi (VIRTUS INTERPRESS, 2015)
The aim of this paper is to examine the effectiveness of board monitoring mechanisms in Government Linked Companies (GLCs) in Malaysia. Mainly it focuses on how the introduction of the transformation policy, which emphasizes strengthening the board effectiveness, would lead to an improvement in the performance of GLCs. Our study goes further to explain the impact of earnings management on performance as it is opined that the performance of the firm could be affected by the earnings management (EM) practices, and, hence, looking at the performance after stripping away the managed portion of performance could provide more accurate results concerning the impact of corporate governance on performance. Using regression analysis, the findings of the study showed that the adjusted R2 increased from 14.8% to 26.8% (between the pre-transformation and post-transformation models). In addition, more corporate governance variables were found to be significant in the post-transformation model (i.e. board independence and board meetings). More importantly, the significance of the variables are as predicted in the hypotheses, thus lending support for the argument of the agency theory. This study has recognized a few limitations. First, the main limitation of the study is that the data were collected through publicly available data which include annual reports and other databases such as Bloomberg. Other data such as qualitative information could be helpful to gain more insight concerning the issue of the effectiveness of the transformation policy. Second, although we are using all available data for the Malaysian GLCs, the sample size of 35 companies could still be considered as a small sample size for generalization purpose. The government, in its role of regulating the corporate governance for GLCs, could gain an insight from the results of the study, thereby providing empirical support for the development of new regulations and recommendations, and takes the necessary corrective decisions regarding the effectiveness of the transformation policy. The paper provides further evidence concerning the relationship between performance and corporate governance mechanisms. Specifically, it looks into such a relationship within the Malaysian GLCs after the introduction of the transformation programme. The results of the study are more accurate for interpretation as the measure of performance has deducted the portion of managed earnings.